The Role of High-density Lipoprotein in Oral and Dental Diseases - Sadeghalbanaei, Leila; Shirban, Farinaz; Bagherniya, Mohammad; Sathyapalan, Thozhukat; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2023)
High-density lipoprotein (HDL) is the smallest and densest of the lipoproteins. Beyond its well-known cardiovascular protective function, it has other actions, including structural function, anti-inflammatory, antioxidant, anti-thrombotic effects, transport of bioactive molecules, and induction of signal transduction pathways. Further, there is a mutual connection between oral health and general health. Hence HDL could be a potentially crucial factor relating oral health to general health. As far as we know, no comprehensive study has been carried out to date, which has explored the association between HDL concentration and oral diseases including lichen plan, recurrent aphthous ulcers, candidiasis, implant osseointegration, oral cancer and precancerous conditions. Here in this review, we summarized the relationship between HDL and oral health, suggesting a significant association between HDL concentration and oral health.
Keywords: dental health